(untitled) (Research, Society and Development, 2022)
The Ministry of Health approved dual therapy (lamivudine associated with a second antiretroviral) as a therapeutic option in the contraindication to the use of other available Nucleoside Analog Reverse Transcriptase Inhibitors - NRTIs (tenofovir, abacavir and zidovudine) due to toxicity, if patients are virological suppression. This study aims to evaluate the effectiveness of therapeutic simplification with lamivudine/dolutegravir (3TC/DTG) in HIV patients on antiretroviral therapy (ART). Retrospective study of the real-life experience in the clinical practice of a simplified scheme with 3TC/DTG in a referral hospital for infectious diseases. We evaluated 76 patients using 3TC/DTG, with a mean age of 56.4 years, 50 (65.8%) of whom were male, mean use of the simplified regimen of 12 months, mean CD4 count = 669.5 cells/ mm3 and average CD8 = 941.5 cells/mm3. Evaluation of viral load after simplification in 67 patients, 63 (94.0%) with maintained virological suppression (<40 copies) and 4 (6.0%) with detected viral load. Among these patients without complete virological suppression, two reported good adherence and the other two described poor adherence in the medical records. The current study confirms the effectiveness of virological suppression in real-life therapeutic simplification with 3TC/DTG. Therapeutic simplification with this regimen is a safe strategy as an option for patients with toxicity or intolerance to regimens containing NRTIs. Long-term studies are needed to confirm the maintenance of efficacy for longer periods of time.